2018
DOI: 10.18632/oncotarget.25304
|View full text |Cite
|
Sign up to set email alerts
|

Additive analgesic effect of dexmedetomidine and dezocine administered intrathecally in a mouse pain model

Abstract: BackgroundIt is known that dexmedetomidine can reduce opioid requirements and that there is a synergistic effect when dexmedetomidine and morphine (a full mu opioid receptor agonist) are administered together. However, it was unclear whether a synergistic or additive effect would be observed when dexmedetomidine was co-administered with a partial mu opioid receptor agonist. The present study was designed to elucidate such effects by intrathecally co-administering dexmedetomidine and dezocine, a partial mu rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another study showed that dezocine in dose of 0.625-2.5 μg (it) significantly increased tail withdrawal latency for C57 mice [24]. Huang with colleagues also demonstrated that dezocine increased tail withdrawal latency within the dose range of 0.3125-1.25 μg (it) and produced highest effect around 43% [17].…”
Section: Thermal Painmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study showed that dezocine in dose of 0.625-2.5 μg (it) significantly increased tail withdrawal latency for C57 mice [24]. Huang with colleagues also demonstrated that dezocine increased tail withdrawal latency within the dose range of 0.3125-1.25 μg (it) and produced highest effect around 43% [17].…”
Section: Thermal Painmentioning
confidence: 94%
“…The analgesic effects of dezocine have been demonstrated in a number of preclinical behavioral paradigms. The literature is reviewed here, particularly focusing on the effects of dezocine on acute and chronic pain with varying experimental conditions on behavioral outcomes [15][16][17][18][19]. The relevant studies are shown in Table 3.…”
Section: Analgesic Activities In Animalsmentioning
confidence: 99%
“…There are three highly homologous subtypes of the α 2 -adrenoceptor: α 2 A, α 2 B, and α 2 C. Dexmedetomidine, a highly selective α 2 -adrenoceptor agonist, has been used for conscious sedation and as an adjunct for clinical anesthesia [ 8 9 10 ]. In animal experiments, dexmedetomidine has been shown to produce analgesic effects in models of neuropathic pain, but the mechanisms underlying these effects remain largely unknown [ 11 12 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with morphine, the gold-standard analgesic, dezocine exhibits less physiological dependence, analgesic tolerance, and hyperalgesia [12]. Huang et al [13] reported that 4 dezocine combined with dexmedetomidine has an additive dose-dependent analgesic effect in a mice model of pain. Wu et al [14] reported that dezocine can inhibit the internalization of the κ-opioid receptor induced by agonists and weaken the activation of astrocytes and dependence of rat models on opioid drugs.…”
Section: Introductionmentioning
confidence: 99%